(untitled) (Fiep Bulletin - online, 2015)
The purpose of this study was to examine the relation between adiposity indexes in a male population. The sample was composed by 440 males aged between 30-38 years old and they were visitors of the coast of the Parana state. The WHO (1997) reference was used to classify BMI. Body density was calculated by the predictive equation of JACKSON & POLLOCK (1978) with three skinfolds and the fat percentage (% G) by the equation of SIRI (1961). The BMI obesity group had the risk indexes for the development of cardiovascular disease higher than the BMI overweight group and this higher than the BMI normal group. Blood pressure, fat percentage and waist circumference were different among the three groups of the BMI, (p = 0.05). There were significant correlations among the overweight and obesity indexes (BMI, fat percentage, waist circumference) and of these indexes with the lean body mass. Hence, the BMI in the studied population was sensitive to detect significant variations among the comportments of the risk factors for the development of the cardiovascular disease studied, significant variance and correlations with the overweight and obesity indexes and the standard error of estimative of the fat percentage by the BMI was not elevated.